Makkah healthcare cluster response, challenges, and interventions during COVID-19 pandemic: A qualitative study - Turky J. Arbaein; Khulud K. Alharbi; Afrah A. Alfahmi; Khawlah O. Alharthi; Sarah S. Monshi; Ali M. Alzahrani; Sanaa Alkabi (Elsevier, 2024)
Background: The global COVID-19 crisis has underscored the critical role of effective decision-making in healthcare systems. Saudi Arabia has shown resilience by implementing comprehensive testing, tracing, and vaccination measures. Given the unique cultural and religious characteristics of Makkah, specific challenges have prompted efforts to uncover local pandemic responses. This qualitative assessment aims to delineate the challenges faced by decision-makers during COVID-19 in Makkah and identify key interventions implemented by the Makkah healthcare cluster to manage and coordinate care. Method: Utilizing a purposive sampling approach, executive leaders within the Makkah Healthcare Cluster were invited for semi-structured interviews during the COVID-19 period. Thematic analysis was carried out in five steps, ensuring rigor and trustworthiness through multiple checks, and employing a critical and collaborative approach. Result: Throughout the COVID-19 outbreak in Makkah, participants revealed Several factors that have hindered healthcare organizations' ability to effectively manage the pandemic, including testing difficulties, resource shortages, vaccination misconceptions, continuity of care issues, infections among healthcare workers, and the need for consistent protocols. The participant leaders in Makkah's healthcare cluster specified implemented strategies that helped in overcoming the encountered challenges, such as adopting new technologies, enhancing communication, managing supply and demand, and improving workforce adaptability and development. Their experience in managing Hajj and Umrah provided valuable insights for handling the pandemic effectively. Conclusion: The study emphasizes the significance of technology adoption, effective communication, supply management, workforce development, and lessons from managing religious events. Its findings have implications for healthcare systems globally, emphasizing the importance of preparedness, response, and resilience in diverse cultural contexts.